Comparison between ultrasound and MRI in antenatal diagnosis of adherent placenta - Natarajan, Sundari; Nagarajan, Deepika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Placental imaging using ultrasonography and MRI with various parameters provides information about abnormal placentation. Prenatal diagnosis of placenta accreta spectrum disorder (PAS) is of paramount importance to minimize complication rate and improve outcome of delivery. The aim of our study is to compare the accuracy between ultrasound and MRI in antenatal diagnosis of adherent placenta. Methods: Prospective study was conducted on 50 pregnant women with persistent placenta previa (after 28 weeks of gestation) at Madurai Medical college and Government Rajaji Hospital for period of 18 months. All patients underwent grey scale and doppler USG and MRI. Hemodynamically unstable patients were excluded from the study. Results: Out of 50 patients of placenta previa, 21 patients were found to have adherent placenta intraoperatively which was subsequently confirmed by HPE. Of this, 16 patients were found to have placenta accreta, 2 patients were found to have placenta increta and 3 patients were found to have placenta percreta. USG predicts possibility of accreta spectrum in 14 out of 21 patients (67% sensitivity). In addition to grey scale ultrasound alone, combined grey scale and colour doppler ultrasound increases sensitivity to 71.4%. MRI predicts possibility of accreta spectrum in 21 out of 21 patients (100% sensitivity). Taking important parameter of retroplacental myometrial thinning in both USG and MRI, specificity approaches 100%. Conclusions: MRI was a confirming tool for all cases suspected to have placenta accreta spectrum disorders and has higher sensitivity when compared to ultrasonography.